Analysis of the Influence of Perceived Value, E-WOM, and Digital Promotion on Purchase Intention of Electric Vehicles - Ninda Rachmawati; Muhammad Iqbal Fajri; Rudy Max Damara Gugat; Riesna Apramilda; Syamsul Hadi; Meutia Nadia Karunia (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study is to investigate the impact of perceived value, electronic word of mouth (E-WoM), and digital promotion on Indonesian consumer purchase intention of electric vehicles. This study was initiated against the backdrop of retrieving the deteriorating environmental situation and conductive marketing strategies promoting purchase consideration of eco-friendly cars. This study is a quantitative research using purposive sampling with 210 participants as samples of consumers, which meet the following requirements: 18 years old and having been staying in Indonesia; have basic understanding of electric vehicle (or EV); and ever search any information or consider to buying it. This data was collected via a 5-point Likert scale questionnaire and analyzed with multiple linear regression. The analysis results indicate that all three independent variables have a positive and significant effect on purchase intention. Perceived value increases purchase intention through perceptions of functional, emotional, and social benefits that are considered greater than the costs incurred. E-WoM strengthens consumer trust through credible positive reviews, while digital promotion drives purchase intention through informative, interactive, and persuasive campaigns. These findings imply that electric vehicle marketing strategies in Indonesia should integrate efforts to enhance perceived value, manage positive E-WoM, and optimize digital promotion to accelerate market adoption.